PENGARUH TERAPI KELOMPOK SUPORTIF UNTUK MENINGKATKAN OPTIMISME PADA PASIEN GAGAL GINJAL KRONIK YANG MENJALANI HEMODIALISIS - Salma Dias Saraswati; Yayi Suryo Prabandari; Rr. Indahria Sulistyarini (Universitas Islam Indonesia, 2019)
This research aims to observe the effectiveness of supportive group therapy to improve the optimism of patients with chronic renal failure undergoing the hemodialysis. The subject was divided into the experimental group (n= 4) and control group (n = 4). The research design was pre-test post- test control group and was measured by three times (pre-test, posttest and follow-up for two weeks). Life Orientation Test (LOT-R) developed by Scheier and Carver (1985) was the measurement tools used to measure the optimism. The training module was arranged based upon the supportive group theory by van den Heuvel, et al (2002). The results showed that the subject in the experimental group had a significant increase in the optimism score in comparison to the control group that was given no supportive group therapy. The implication and limitation in the research finding would be the discussion.